Biosynthesis-based metabolomics analysis reveals chemical diversity between two Salvia species - Wang, Feiyan; Li, Chenyi; Yu, Haizheng; Yang, Dongfeng; Ye, Ji; Zhang, Lei (Frontiers in Plant Science, 2025)
Salvia officinalis is an important dietary supplement that is widely used as a flavor regulator and plays an important role in the prevention and treatment of neurodegenerative diseases. Salvia miltiorrhiza Bunge is a famous Chinese herbal medicine for treating cardiovascular diseases. Secondary metabolites with diverse structures endow the two species with various edible and medicinal values. However, the differences in secondary metabolites between the leaves of S. officinalis and S. miltiorrhiza are still unclear. Herein, FlavourSpec® combined with spatial metabolomics was used to explore the distribution patterns of secondary metabolites including volatile and non-volatile components. The results indicated that the chemical compositions of the two Salvia species were significantly different. Specifically, S. miltiorrhiza Bunge contained high levels of phenolic acid components with a furan ring that can hardly be detected in S. officinalis. The volatile small molecules as well as carnosic acid and its derivatives were found to be major components of S. officinalis leaves. Because of the long-term exposure of leaves to ultraviolet radiation and the same environmental stress, carnosic acid and its derivatives exhibit widespread distribution characteristics in S. officinalis leaves. The work explored the similarities and differences in secondary metabolites of S. officinalis and S. miltiorrhiza Bunge, providing not only the material basis to develop the application value in dietary nutrition, but also a theoretical foundation for the development and utilization of medicinal resources of Salvia.